LOW-RANK COAL GASIFICATION USING A BUBBLING FLUIDIZED BED REACTOR AT LOW OPERATING TEMPERATURE - Sapta Rianda; Dedy Yaskuri; M. Ade Andriansyah Efendi (Indonesian Mining Journal, 2019)
Coal gasification is one of coal utilizations that produces less CO2 emission than coal combustion. Coal gasification technology that has been used in Indonesia is  generally a fixed bed gasification. Fixed bed is designed for high-rank coal and the majority of Indonesian coal is of a low-rank. Low ash and high moisture content of the Indonesian coal in a fixed bed can affect mechanical and thermal fragmentation, pressure drop, gas and particle flow distribution. The operation of gasifier may cause unstable condition. Another gasification technology is bubbling fluidized bed, which is operated above 1,200°C, so ash can melt. High operating temperature causes agglomeration and makes unstable gasification process. Therefore, in this study, low-rank coal is gasified in bubbling fluidized bed reactor at low operating temperature. The purpose of this study is to determine the optimal conditions of bubbling fluidized bed gasification. The research was conducted in bubbling fluidized bed coal gasification Process Development Unit (PDU) at Coal Utilization Technology Centre of R&D Centre of tekMIRA, Palimanan. Coal was fed continuously as many as 20 kg/hour into a gasifier then was gasified to produce gas using air as a gasifying agent and silica sand as a bed material at 850- 950°C. The produced gas from the gasification was analyzed using the Orsat Analyzer. A simulation using a ChemCAD 7.1 CC steady state was applied to validate the experiment result. From the analyzed result of yield gas composition, the produced CO and CO2 were about 10-15 wt%. Gas compositions that are close to criteria of producer gas, no agglomeration, and stable process condition during study indicate that bubbling fluidized bed gasification at low operating temperature is suitable to be applied as gasification technology for Indonesian low-rank coal.